Intravenous levetiracetam: a new treatment alternative for refractory status epilepticus. Issue 6 (15th May 2009) - Möddel, G; Bunten, S; Dobis, C; Kovac, S; Dogan, M; Fischera, M; Dziewas, R; Schäbitz, W-R; Evers, S; Happe, S
Abstract : The purpose of this study was to investigate the safety and efficacy of intravenous levetiracetam (LEV-iv) in refractory status epilepticus (SE). A retrospective chart review was performed on patients who received LEV-iv for treatment of SE (n = 36) and had failed at least one other antiepileptic drug. LEV-iv (median 3000 mg/day; range 1000–9000) was administered as a bolus loading (500–2000 mg per 30–60 min, n = 30) or as a continuous pump infusion (n = 6). SE was terminated in 69% ("responders"); 31% ("non-responders") remained in SE. Factors associated with failure were: dose escalation over 3000 mg/day, lack of bolus loading, treatment latency over 48 h, age over 80 years, non-convulsive SE with coma ("subtle SE"), periodic lateralised epileptiform discharges (PLEDs) on EEG, acute cerebral lesion and intubation narcosis. SE was terminated in all eight patients without brain lesion (p = 0.033), and in all seven patients with complex partial SE (p = 0.051). Outcome was favourable (ambulatory patients) in 48% (responders) compared with 0% (non-responders), and "adverse" (death or continuing coma/stupor) in 24% (responders) compared with 100% (non-responders). Mortality was 17% (responders 4%, non-responders 45%). No patient had cardiocirculatory side effects or worsening of SE. Two patients experienced nausea and vomiting during LEV-iv loading, leading to aspiration pneumonia in one. This study suggests that LEV-iv may be a safe and efficacious treatment of SE. Prospective and controlled trials are imperative to confirm these preliminary findings.